(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
During the current research on 73 individuals of Fistularia commersonii from 27-11-2022 To 19-10-2024 caught from (Ras Al-Basit 35°50′57.62″ N, 35°50′11.47″ E), Syrian marine waters. The qualitative and weight composition of the food elements in food spectrum of F.commersonii were studied. In addition to some biological factors (Condition factor, General Fullness factor and Frequency of occurrence). The results showed that the food spectrum of F.commersonii consists of more than /13/ nutritional elements, (12) species belonging to fish and one species of Crustaceans. Fishes were the first among to rely on and represented by (12) species, Atherinomorus lacunosus species which belongs to Atherinidae family, the most abundant species of this Family. The Labridae family were in the second level represented by three species Halichoeres bivittatus, Symphodus melanocerus, Coris julis. The Mullidae family species Especially Parupeneus forsskali, Mullus barbatus & the Apogonidae family species Cheilodipterus pygmaios, Apogon nigripinnis were in the third level followed by the Chromis Chromis. There were not any big differences in structure of food spectrum with regards to the length or sex differences among the studied fish.